Framing of femininity: A cognitive study of gendered metaphors in brand advertisements - Amna Aziz; Xu Wen; Muhammad Khizar Hayat Naeem; Suman Naeem (Acta Psychologica)
This study delves into the metaphorical representation of women in advertising and its impact on consumer perceptions, grounded in Cognitive Metaphor Theory (CMT) as the guiding framework. By adopting a multimethod approach, the analysis combines Fairclough's three-dimensional model of Critical Discourse Analysis (CDA) and Structural Equation Modeling (SEM) to explore advertisements across various sectors, including fashion, cosmetics, sportswear, and automotive. The research uncovers three dominant gendered metaphorical categories: Women as Objects (WAO), Women as Nature (WAN), and Women as Animals (WAAN). The qualitative findings reveal that WAO metaphors contribute to the objectification of women, reducing them to passive, aesthetic beings, thereby negatively influencing the Overall Brand Perception (OBP). Contrarywise, WAN analogies highlight genuineness and natural beauty, although they may inadvertently reinforce conventional gender roles associated with care and passivity. WAAN metaphors were the most effective, portraying women as empowered and self-governing, hence significantly boosting OBP. SEM results demonstrated that gender influenced the interpretation of these metaphors, with women exhibiting a greater negative response to WAO metaphors and a more favorable response to WAN and WAAN metaphors. The research emphasizes the twin function of gendered metaphors in advertising: as cognitive instruments that reduce intricate concepts and as cultural narratives that influence societal standards. The results underscore the necessity for advertisers to prioritize inclusive and powerful depictions of women in accordance with modern principles of gender equality and diversity.